The Absent Presence of the State in Large-Scale Resource Extraction Projects - Nicholas A. Bainton; Emilia E. Skrzypek (Australian National University Press, 2021)
Standing on the broken ground of resource extraction settings, the state is sometimes like a chimera: its appearance and intentions are misleading and, for some actors, it is unknowable and incomprehensible. It may be easily mistaken for someone or something else, like a mining company, for example. With rich ethnographic material, this volume tackles critical questions about the nature of contemporary states, studied from the perspective of resource extraction projects in Papua New Guinea, Australia and beyond. It brings together a sustained focus on the unstable and often dialectical relationship between the presence and the absence of the state in the context of resource extraction. Across the chapters, contributors discuss cases of proposed mining ventures, existing large-scale mining operations and the extraction of natural gas. Together, they illustrate how the concept of absent presence can be brought to life and how it can enhance our understanding of the state as well as relations and processes forming in extractive contexts, thus providing a novel contribution to the anthropology of the state and the anthropology of extraction.
Keywords: 300; Public administration; Regional government policies; Environmental economics; Mining industry; Construction & heavy industry; Resource Extraction; State; Absent Presence; Papua New Guinea; Australia